Penggunaan Film Anime Cells AT Work yang Dipadukan dengan Writing Is Thinking dalam Mempengaruhi Penguasaan Konsep Siswa Pada Materi Sistem Imun - Fitriani Nurpratiwi Susanto; Adi Rahmat; Didik Priyandoko (Postgraduate, University of Mataram, 2023)
After the pandemic, people have become more concerned about the immune system. Immune system material is also studied in class XI in Biology. Unfortunately, immune system material is material that is difficult for students to learn because its abstract concepts with high complexity cause an increase in cognitive load on the ICL and ECL components which results in students' ability to master the Immune System concept being low. This research aims to obtain information regarding the influence of the anime film Cells at Work and Writing Thinking on students' cognitive load and mastery of concepts in the immune system material. This research uses descriptive research. The research method used was a quasi-experiment with a pre-test and post-test design. The research population is class XI students at SMAN 4 Cimahi for the 2022/2023 academic year. Sampling was conducted using Purposive Sampling so that class X1 MIPA-2 was obtained as the experimental class and class X MIPA-6 as the control class. The subjective rating scale instrument is used to measure cognitive load, while to measure concept mastery, reasoned multiple choice (two-tier multiple choice) is used to obtain data on concept mastery. Based on the results of research on the cognitive load aspect, it shows that with the use of the anime film Cells at Work combined with Writing is Thinking, there is a significant difference in scores on the lower ECL component and there is an increase in learning outcomes (GCL) compared to the control class. In line with the increase in GCL, there was a significant increase in mastery of concepts in the cognitive domains C2 (understanding), C3 (applying), and C4 (analyzing).